Mortal follies : Episcopalians and the crisis of mainline Christianity - Murchison, William P. (Encounter Books, 2009)
It's not that the dignified and rarefied old Episcopal Church quit believing in God. It's that the God you increasingly hear spoken of in Episcopal circles is infinitely tolerant and given to sudden changes of mindnot quite the divinity you thought you were reading about in the scriptures. Episcopalians of the twenty-first century, like their counterparts in other churches of the so-called American mainlinesuch as Methodists and Presbyteriansseem to prefer a God that the culture would be proud of, as against a culture that God would be proud of. While they work to rebrand and reshelve ortho.